2008
DOI: 10.1108/10662240810912747
|View full text |Cite
|
Sign up to set email alerts
|

“Usability + usefulness = trust”: an exploratory study of Australian health web sites

Abstract: Purpose -The aim is to explore users' reactions to health information web sites from the perspective of trust, retrieval of relevant information and ease-of-use, and to establish the link between perceived quality, trust, and usability. Design/methodology/approach -An analysis of three Australian health web sites was undertaken. A usability test was conducted on those three web sites resulting in 207 completed user evaluations. The evaluations included both quantitative and qualitative data. Findings -The thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 33 publications
1
36
0
3
Order By: Relevance
“…Trust has been found to affect user adoption of various services, such as online news services (Chen & Corkindale, 2008), Internet banking (Flavian, Guinaliu & Torres, 2005), health web sites (Fisher, Burstein, Lynch & Lazarenko, 2008), and mobile shopping (Lu & Su, 2009). Trust includes initial trust and continuance trust.…”
Section: Initial Trust and Perceived Ease Of Usementioning
confidence: 99%
“…Trust has been found to affect user adoption of various services, such as online news services (Chen & Corkindale, 2008), Internet banking (Flavian, Guinaliu & Torres, 2005), health web sites (Fisher, Burstein, Lynch & Lazarenko, 2008), and mobile shopping (Lu & Su, 2009). Trust includes initial trust and continuance trust.…”
Section: Initial Trust and Perceived Ease Of Usementioning
confidence: 99%
“…The relevance, quality, usefulness and accuracy of information are known determinants that the information content is trustworthy [36]. The presentation, ease of use and clarity of information are linked to perceptions of 'professionalism' that, again, underpin judgements of trust [37]; [4]; [38] and, finally, the beliefs about objectivity and impartiality of the source also ensure trust [15], [16].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the trust placed in health websites might be fundamentally different from the trust placed in e-commerce websites. Only three of the definitions used in the reviewed body of work were made specific to trust in websites, with two definitions specific to trust in health websites (Rains, 2009, Bliemel and Hassanein, 2007, Fisher, 2008). (See Table 2 for definitions.)…”
Section: Discussionmentioning
confidence: 99%
“…Rains and Karmikel (2009) proposed a two-part model of how perceptions of persuasion and social influences impact credibility. The last model by Fisher et al (2008) is similar to that of Rains and Karmikel in that it evaluated design elements that impacted trust. Their model demonstrated that retrieving relevant information and ease of use contributes to quality and trust perceptions.…”
Section: Discussionmentioning
confidence: 99%